Participatory Relationships in the Thanksgiving Prayers of Anglican Eucharistic Liturgies: A Case Study in the Church of England and the Anglican Church of Australia. (March 2021) - Douglas, Brian
This article examines the participatory relationships in the Thanksgiving Prayers of the Eucharist in two provinces of the Anglican Communion: the Church of England and the Anglican Church of Australia. Two types of participatory relationships are discussed: those between the body and blood of Christ and the elements (known as BBE), and those between the body and blood of Christ and the communicants (known as BBC). It is noted that both of these types of participatory relationship have been and are found in Anglican Thanksgiving Prayers but a balance between the two has not always been found due to a preference for particular eucharistic theologies. In some Thanksgiving Prayers BBE relationships are excluded or muted in order to lessen any realist notions of Christ's presence in the Eucharist. Some Anglican liturgical history is considered along with modern liturgies to assess how these relationships are used. Recommendations for a balanced use of both relationships are made.